Towards a user-oriented approach in the design and planning of public transport interchanges - Schalekamp, Hertzog Venter (Centre for Transport Studies, 2014)
Public transport provision in South Africa is set to change dramatically in the coming years if the plans and strategies of Government come to fruition. Policy clearly states that the needs of the end user of public transport services and facilities have to be prioritised, and that transport systems will be overhauled to provide a range of integrated trunk and feeder services, in emulation of the successes achieved in the so-called public transport 'model cities' of South America. However, it is not certain whether the range of public and private institutions involved in the planning, implementation and operations of public transport at the local level are ready to respond effectively to the policy requirements. Institutional fragmentation is the order of the day, public transport services are largely peak-time, commuter based services, and the minibus taxi industry remains effectively unregulated. The experience of public transport users, if measured by the efficiency of transferring between services at public transport interchange facilities, is of a very poor quality, and the design and planning guidelines for these facilities do not offer much insight into how this situation can be rectified. This dissertation provides two insights in view of the current challenging public transport reality. Firstly, it investigates the link between institutional integration, and whether such integration has an effect on the experience of public transport users at interchanges. Secondly, it critically analyses the existing design and planning guidelines for public transport interchanges to explain why these documents do not seem to lead to improved physical integration between transport services, and ultimately an improved experience for the person wishing to transfer between those services. These links are tested by developing a framework that assesses the obstacles that reduce the efficiency of user transfers between services at interchanges, and it applies this framework at interchange sites in Cape Town in South Africa, and Curitiba and Sao Paulo in Brazil. The findings, when compared between sites and cities, lead to the formulation of recommendations regarding the expectations surrounding institutional integration and the provision of more effective design and planning guidelines for public transport facilities.